The Relationship between the Level of Knowledge about Cervical Cancer and Motivation for HPV Vaccination among Women of Reproductive Age - Rinawati, Siti Mardiastuti; Soraya, Soraya; Ariwati, Valentina Dili; Augusaskiani, Mutiara Alif; Nufus, Hayatun (Yayasan Ahmad Mansyur Nasirah, 2025)
Cervical cancer is the second leading cause of death among women in Indonesia, with approximately 99% of cases caused by Human Papillomavirus (HPV) infection. Although HPV vaccination is effective in preventing this disease, its acceptance rate in the community remains relatively low. This study aimed to analyze the relationship between the level of knowledge about cervical cancer and motivation to undergo HPV vaccination among women of reproductive age at Prostasia Clinic. This study employed an analytical survey design with a cross-sectional approach. The sample consisted of 85 women of reproductive age at Prostasia Clinic, selected using purposive sampling techniques. Data were collected through validated questionnaires and analyzed using the Chi-Square statistical test. The results showed that the majority of respondents had a good level of knowledge (54.1%) and high motivation for HPV vaccination (61.2%). Bivariate analysis indicated a statistically significant relationship between knowledge level and motivation for HPV vaccination, with a p-value of 0.009 (p < 0.05). Adequate knowledge regarding the risks and prevention of cervical cancer was found to be a strong motivating factor for women to undergo vaccination. These findings highlight the urgency of continuous health education to increase HPV vaccination coverage in order to achieve the 2030 cervical cancer elimination target.